Domestic Violence during the COVID-19 Pandemic in Portugal - Ana Gama; Ana Rita Pedro; Maria João Leote de Carvalho; Ana Esteves Guerreiro; Vera Duarte; Jorge Quintas; Andreia Matias; Ines Keygnaert; Sónia Dias (Karger Publishers, 2021)
The measures implemented to combat the COVID-19 pandemic led populations to confinement at home, with increased risk of domestic violence due to extended shared time between victims and offenders. Evidence on domestic violence in times of pandemic is lacking. This study examines the occurrence of domestic violence, associated factors and help seeking during the COVID-19 pandemic. An online survey was conducted in Portugal between April and October 2020 by NOVA National School of Public Health. The survey was disseminated through partner networks, media, and institutions working within the scope of violence. Data were collected on the experience of domestic violence, and help seeking during the pandemic. In a total of 1,062 respondents, 146 (13.7%) reported having suffered domestic violence during the pandemic, including psychological (13.0%, n = 138), sexual (1.0%, n = 11), and physical (0.9%, n = 10) abuse. Overall, the lower the age, the more the reported domestic violence. Also, a higher proportion of participants who perceived difficulties to make ends meet during the pandemic reported domestic violence. Differences between women and men and across educational levels on reported domestic violence were not statistically significant. Bivariate logistic analyses showed that, among women, reported domestic violence was more likely among those with up to secondary education compared to higher education. Most of the victims did not seek help (62.3%), the main reasons being considering it unnecessary, that help would not change anything, and feeling embarrassed about what had happened. Only 4.3% of the victims sought police help. The most common reasons for not coming forward to form a complaint were considering the abuse was not severe and believing the police would not do anything. Our findings indicate that domestic violence during the COVID-19 pandemic was experienced by both sexes and across different age groups. There is a need for investing in specific support systems for victims of domestic violence to be applied to pandemic contexts, especially targeting those in more vulnerable situations and potentially underserved.